2020
DOI: 10.31289/jimbi.v1i2.401
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Leverage Dan Pertumbuhan Perusahaan Terhadap Profitabilitas (Roe) Pada Perusahaan Property Real Estate Yang Terdaftar Di Bei (2014 – 2018)

Abstract: The purpose of this study was to determine the effect of leverage and company growth on profitability (ROE) in property and real estate companies listed on the IDX. This type of research is a saturated sample, which is a sampling technique that when an entire population is used as a sample. Population of this study is a total of 12 companies that contain data on financial statements of real estate property companies listed on the Stock Exchange during the 2014-2018 period. The analysis technique used is multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…This study is consistent with studies done by Mardiah & Nurulrahmatiah, (2020) and (Wijaya, 2012) However, this research has not in line with the results of the study conducted by (Rosida & Aisyah, 2021;Widiyanti & Bakar, 2014).…”
Section: The Effect Of Working Capital Turnover On Profitabilitysupporting
confidence: 84%
“…This study is consistent with studies done by Mardiah & Nurulrahmatiah, (2020) and (Wijaya, 2012) However, this research has not in line with the results of the study conducted by (Rosida & Aisyah, 2021;Widiyanti & Bakar, 2014).…”
Section: The Effect Of Working Capital Turnover On Profitabilitysupporting
confidence: 84%
“…Different results may arise if the company plans for high liquidity as working capital in anticipation of shortterm debt payments or a portion of long-term debt that must be paid immediately (Muslih, 2019). Based on research conducted by Angelina et al (2020) and Wedyaningsih et al (2019), states that CR affects profitability but differs from the results of research from Widiyanti & Bakar (2014), which says that CR does not affect profitability.…”
Section: Liquidity Indicates a Company's Ability To Meet Its Financialmentioning
confidence: 99%
“…The effect of corporate social responsibility… research by Widiyanti & Bakar (2014), which found that the current ratio cannot affect profitability. This means that the higher number of current ratios in a company can not affect the company's profitability.…”
Section: Effect Of Current Ratio On Profitabilitymentioning
confidence: 99%
“…However, the results of this researcher are different from the research conducted by Anggarsari & Aji (2018), which shows that leverage does not affect profitability. Andayani (2020) add that leverage ratio or solvency ratio is the use of a company's financial assets and resources, consisting of fixed costs, with the aim of increasing the potential return of its shareholders.…”
Section: Introductionmentioning
confidence: 99%
“…A high DAR value can indicate high risk. This is because companies are worried that they will not be able to cover total liabilities with their own assets, making it increasingly difficult to obtain additional credit (Andayani, 2020).…”
Section: Introductionmentioning
confidence: 99%